(untitled) (Marketing Journal, 2025)
This study provides an in -depth analysis of enhancing the effectiveness of marketing strategies in oilseed crop production. Based on both global and Uzbekistan - specific experiences, it explores the role of digital technologies, contract farming, cooperativ es, and social media platforms. Statistical and comparative methods were used to evaluate the efficiency of the marketing system across all stages from production to consumption. As a result, strategic directions aimed at increasing income, reducing costs, and optimizing the value chain were identified. Practical recommendations tailored to the conditions of Uzbekistan were developed.